2022
DOI: 10.5539/jedp.v13n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Relationship Between Metacognitive Monitoring and Reading Comprehension

Abstract: Metacognitive processes are crucial components of self-regulatory ability. The study examined the developmental relationship between metacognitive monitoring and reading comprehension using longitudinal data from the National Educational Panel Study (NEPS) in Germany. We used a cross-lagged panel analysis – in the framework of Structural Equation Modeling–to examine the reciprocal relationship between metacognitive monitoring (assessed as a retrospective judgement of one’s perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…In math, we found that across the achievement distributions, gender differences emerged as early as the fall and spring of kindergarten at the top of the achievement distribution and spread throughout the distribution during the primary schooling years. This result replicated the previous finding using another cohort of the ECLS-K: 1999, that is, the underrepresentation of girls at the top of the distribution (Cimpian et al, 2016;Edossa et al, 2022;Penner & Paret, 2008;Robinson & Lubienski, 2011). Considering effect size analyses, the present study reveals that females inconsistently overtake males at the bottom of the distributions.…”
Section: Discussionsupporting
confidence: 91%
“…In math, we found that across the achievement distributions, gender differences emerged as early as the fall and spring of kindergarten at the top of the achievement distribution and spread throughout the distribution during the primary schooling years. This result replicated the previous finding using another cohort of the ECLS-K: 1999, that is, the underrepresentation of girls at the top of the distribution (Cimpian et al, 2016;Edossa et al, 2022;Penner & Paret, 2008;Robinson & Lubienski, 2011). Considering effect size analyses, the present study reveals that females inconsistently overtake males at the bottom of the distributions.…”
Section: Discussionsupporting
confidence: 91%
“…(Medranda, et al, (2023). On the other hand, Edossa et al, (2022) stated that students' ability to evaluate accurately was shown to be positively and reciprocally associated with understanding what they are reading, a multi-group cross-lagged panel analysis revealed that excessive underestimation had a more negative impact on subsequent reading comprehension compared to excessive overestimation. Cai et al (2023) examined the developing relationships between aim, metacognitive approach, and school accomplishment.…”
Section: Introductionmentioning
confidence: 96%